2016
DOI: 10.15243/jdmlm.2016.041.681
|View full text |Cite
|
Sign up to set email alerts
|

Application of perennial legume green manures to improve growth and yield of organic lowland rice

Abstract: Abstract:A pot experiment in green house was done to study the effect of the dosage and speciesof perennial legume green manures to the physiological traits, growth and yield of organic lowland rice (Oryza sativaL.), and to obtain the optimal dosage as well. The research was arranged in a factorial randomized block design consistedof two factors with three replications.The first factor was the species of perennial legume thatconsisted of threespecies: Turi (Sesbaniagrandiflora), Glirisidia (Gliricidiasepium), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
4
0
4
Order By: Relevance
“…Besides, 50% of applied nitrogen, faster decomposition rate and better nutrient release from Gliricidia tree leaves might be associated with improved soil fertility that helps to improve plant growth in terms of plant height. Winarni et al (2016) demonstrated that the rice plant height was better in Gliricidia leaves-treated pots compared to that of cowdung-treated pots, which considered as control treatment.…”
Section: Performance Of Tomatomentioning
confidence: 99%
“…Besides, 50% of applied nitrogen, faster decomposition rate and better nutrient release from Gliricidia tree leaves might be associated with improved soil fertility that helps to improve plant growth in terms of plant height. Winarni et al (2016) demonstrated that the rice plant height was better in Gliricidia leaves-treated pots compared to that of cowdung-treated pots, which considered as control treatment.…”
Section: Performance Of Tomatomentioning
confidence: 99%
“…Pupuk hijau legum tahunan merupakan salah satu pupuk organik yang berpotensi sebagai sumber bahan organik tanah dan unsur hara tanaman padi sawah N. Salah satu jenis pupuk hijau legum tahunan dari jenis Glirisidia memiliki kadar N tinggi dan dekomposisnya cukup cepat. Kandungan kadar N daun Glirisidia segar adalah N 4,14%, daun Glirisidia kering angin 3,13%, daun Glirisidia kering matahari 3,34% dan kompos pupuk kandang sapi memiliki kadar N 1,49% (Winarni, 2016;Winarni, 2018). Nitrogen adalah suatu unsur nutrisi merupakan komponen asam amino, protein, asam nukleat, klorofil, enzim, hormon dan beberapa metabolit esensial lain (Wijaya, 2010;Lakitan, 2012;Sugito, 2012).…”
Section: Pendahuluanunclassified
“…Penelitian yang telah dilakukan oleh Winarni et al (2016) menunjukkan bahwa daun Glirisidia dengan dosis 20 t/ha meningkatkan karakter fisiologis, pertumbuhan tanaman dan hasil panen gabah. Hasil penelitian Winarni (2018) menunjukkan bahwa tidak ada perbedaan pengaruh aplikasi daun Glirisidia dalam bentuk segar, kering angin dan Glirisidia kering matahari.…”
Section: Pendahuluanunclassified
“…To find places where yields may have stagnated, the researchers conducted a global, regional, and national analysis of maize production patterns using green manuring to control pests and diseases of maize [ [20] , [21] , [22] , [23] , [24] , [25] ]. Furthermore, other studies have extensively investigated the use of green manure in crop production for a variety of crops, including rice [ 26 , 27 ], maize [ 28 , 29 ], okra [ 30 ], tomatoes [ 31 ], and wheat [ 32 ]. In addition to boosting crop production, it also decreases the use of chemical fertilizers, consequently increasing soil microbial activity [ [32] , [33] , [34] , [35] ].…”
Section: Introductionmentioning
confidence: 99%